PENGGUNAAN METODE TOTAL PHYSICAL RESPONSE (TPR) UNTUK MENINGKATKAN KOSAKATA BAHASA INGGRIS PADA ANAK USIA DINI - Salwa Arisanti; Herlina; Azizah; Wahira (CV. Kalimasada Group, 2026)
The development of language skills in early childhood usually takes place gradually and naturally starting from infancy to school age. Language development in early childhood can be influenced by biological and environmental factors. This study aims to determine the description of English vocabulary mastery in the experimental group before and after the application of the TPR method and to find out the description of English vocabulary mastery in the control group before and after conventional learning. This study uses a quasi-experimental design method with a pretest-posttest control group design model. The type of research design used is in the form of Nonequivalent Control Group Design, with two research groups, namely the experimental group receiving treatment and the control group. This study uses data collection methods, including observation and documentation. The data analysis process aims to test the hypotheses proposed in this study. For this reason, statistical analysis techniques that are relevant to the research variables are used. This stage of data analysis is taken through: descriptive analysis and non-parametric statistical analysis. The results showed that the initial ability to master early childhood English vocabulary in the experimental group before being given treatment was still at a relatively low level. After learning was applied using the Total Physical Response method, there was a significant increase in English vocabulary skills in the experimental group. This increase is evident both from the results of descriptive analysis and the results of statistical tests, where the average post-test score increases markedly compared to the pre-test score. This shows that the TPR method is able to help children understand and remember vocabulary more effectively.